2010
DOI: 10.1007/s00044-010-9401-7
|View full text |Cite
|
Sign up to set email alerts
|

Major alkaloidal constituent from Impatiens niamniamensis seeds as antihyperglycemic agent

Abstract: Hypaphorine, an a-N,N,N-trimethyltryptophan betaine, is isolated as major constituent from Impatiens niamniamensis seeds (Balsaminaceae) for the first time. The structure of the compound was established by spectroscopic data. This is the first report of its in vivo evaluation for antihyperglycemic activity. The ethanolic extract of the seeds showed mild antihyperglycemic activity at the dose of 200 mg/kg body weight, whereas, hypaphorine showed significant activity in streptozotocin-induced diabetic rats at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…3, treatment with different concentrations of hypaphorine (10 and 50 lM) remarkably inhibited cellular TG accumulation (P < 0.05 or 0.01) (Fig. [21] Effect of Hypaphorine on Expression of Adipocyte-Specific Genes during Adipocyte Differentiation Adipocyte differentiation from 3T3-L1 preadipocytes is associated with the expression of adipocyte-specific genes including PPARc and C/EBPa. 3d) in a dose-dependent manner.…”
Section: Hypaphorine Inhibited Hormone-induced Adipocyte Differentiatmentioning
confidence: 91%
See 4 more Smart Citations
“…3, treatment with different concentrations of hypaphorine (10 and 50 lM) remarkably inhibited cellular TG accumulation (P < 0.05 or 0.01) (Fig. [21] Effect of Hypaphorine on Expression of Adipocyte-Specific Genes during Adipocyte Differentiation Adipocyte differentiation from 3T3-L1 preadipocytes is associated with the expression of adipocyte-specific genes including PPARc and C/EBPa. 3d) in a dose-dependent manner.…”
Section: Hypaphorine Inhibited Hormone-induced Adipocyte Differentiatmentioning
confidence: 91%
“…Traditional Chinese medicine uses the roots, flowers, and seeds of C. korshinskii, for the treatment of high blood pressure, dizziness, menstruation, cancer, and other diseases. [20] A recent study indicated that hypaphorine showed significant antihyperglycemic activity in diabetic rats at the dose of 50 mg/kg body weight, [21] but the mechanism remains unknown. [13] [14] Hypaphorine was first isolated from seeds of C. korshinskii and has been detected in several other higher order plants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations